(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Human resource is required for an organization to conduct different business activities. Without the support of human resource, the organization cannot exist or operate effectively. The success of any organization depends on the effective use of human resources. Human resource is the major contributory force for any kind of organization in India. Due to this, management of this human resource, i.e. Human Resource Development must have more significance in India. Also, human resources are major risky to manage in the construction field, as they are not mostly permanent like other industries. Therefore, it is necessary to analyze the Human Resource development in the construction industry. However, studies have shown that research on develop the resources in the project management context is yet undeveloped and publications are relatively rare and most research simply involves case studies or expert reports. Past research has been done on HRD are mostly qualitative and there is a lack of quantitative research. Due to this lack of quantitative research, there is no good-developed framework for factors affecting HRD in the construction industry. The study recommended that Employee health and safety should consider first for any organization to wants to move further to achieve their objectives. A framework of human resource development has been developed. This framework contains many factors and it is divided in 8 Main Criteria’s as(a)Job Analysis and HR Planning,(b)Recruitment and Selection,(c)Education and Training,(d)Retaining, Motivation and Performance Appraisal,(e)Compensation and Rewards,(f)Employment Relations,(g)Health and Safety,(h)Other External Factors.(I)Labour ProductivityData is collected through questionnaires and personal interviews targeting Engineers, Project Managers, HR Managers and Contractors. International All factors affecting HRD have been ranked using RII and SPSS Method or SWOT Analysis.